Description of Drilocephalobus moldavicus Lisetskaya, 1968 (Rhabditida: Osstellidae) from Kelso Dunes, Mojave National Preserve, California, USA - Boström, Sven; Holovachov, Oleksandr (Zootaxa, 2018)
Specimens of Drilocephalobus moldavicus are described from the Kelso Dunes area, Mojave National Preserve, southern California. This is the first record of the genus in North America. The specimens of this population are characterized by a body length of 322–417 µm in females and 403 µm in the male; cuticle finely annulated; lateral field with five incisures, extending to phasmid and two incisures extending almost to tail terminus in both sexes; lip region helmet-shaped, offset from body contour; lips amalgamated; stoma with thin walls lacking sclerotizations; pharynx without distinct divisions, cylindrical, widening slightly at about 1/3 of its length and basally, without valves; spermatheca 14–19 µm long; postvulval uterine sac 25–27 µm long; spicules 23 µm long; and female tail conoid-elongate with rounded terminus.